Airborne - Mills, DiAnn (Carol Stream, Illinois : Tyndale House Publishers, 2020)
"Heather Lawrence's long-awaited vacation to Salzburg wasn't supposed to go like this. Mere hours into the transatlantic flight, the Houston FBI agent is awakened when passengers begin exhibiting horrific symptoms of an unknown infection. As the virus quickly spreads and dozens of passengers fall ill, Heather fears she's witnessing an epidemic similar to ones her estranged husband studies for a living-but this airborne contagion may have been deliberately released. While Heather remains quarantined with other survivors, she works with her FBI colleagues to identify the person behind this attack. The prime suspect? Dr. Chad Lawrence, an expert in his field . . . and Heather's husband. The Lawrences' marriage has been on the rocks since Chad announced his career took precedence over his wife and future family and moved out. As more victims fall prey days after the initial outbreak, time's running out to hunt down the killer, one who may be closer to the victims than anyone ever expected"--
Keywords: United States -- Federal Bureau of Investigation -- Fiction -- Employees; Virus diseases -- Fiction; Airborne infection -- Fiction; Airplanes -- Fiction; Husband and wife -- Fiction; Thrillers (Fiction); Christian fiction